Hakikat Belajar dan Pembelajaran - Astri Azani; Sarmila Sarmila; Gusmaneli Gusmaneli (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Learning is an activity that is deliberately carried out so that there is a change in one's abilities, by learning children who previously did not know, were unskilled, become knowledgeable and skilled. Meanwhile, learning is a process of interaction between educators and students, and learning resources in educational environmental units. Learning is assistance provided by educators so that knowledge, knowledge and mastery can be acquired. The use of various learning resources in educational institutions is always influenced by various factors, namely internal factors that have a dominant influence on the learning and learning process such as awareness, enthusiasm, attitudes, interests, metacognition, abilities, skills and personal comfort for users; Meanwhile, external factors are those that influence the availability of varied learning resources, ease of access to learning resources, learning processes, space, human resources, as well as traditions and systems currently in force in schools/educational institutions.